Filipinos writing : Philippine literature from the regions - Lumbera, Bienvenido (Pasig City, Philippines : Anvil Publications, 2001)
"Filipinos Writing," as the title of a textbook for Filipino college students being introduced to the literature of their country, represents a challenge both to teachers of literature and literary critics and historians. In the new millennium, at a time when "globalization" in repeatedly invoked as a vision of the future of the world, young Filipinos must be made aware that in all the 78 provinces of their native country, Filipino writers have turned out literary works in eight major Philippine languages, in two colonial languages, and in a variety of little-known ethnic languages. This body of works represents a distinct heritage that has imprinted "Filipino-ness" on our culture, even as its identity is continually developing and being clarified with every writing generation. The literature of the Filipinos, therefore, once introduced into the consciousness of our country of our youths, provides a dynamic base for national pride and self-esteem our people need so they could set their own parameters for participation in inter-nation transaction in a globalized society.
Cordillera Literature -- Northern Luzon Literature -- Pangasinan Literature -- Pampanga Literature -- Central Luzon and Southern Tagalog Literature -- National Capital Region Literature -- Bicol Literature -- Eastern Visayas Literature -- Central Visayas Literature -- Western Visayas literature -- Mindanao Literature -- References.
Includes bibliographical references.
Keywords: FILIPINO POETRY